Pelayanan Akta Kelahiran Pada Dinas Kependudukan dan Catatan Sipil Kota Surabaya - Irwantoro Irwantoro (Matra Pembaruan: Jurnal Inovasi Kebijakan, 2018)
Improving the quality of public services is one of the policy issues in the current era of bureaucratic reform. This has become very important considering the quality of public services since the bureaucratic reforms have been rolled out there have been improvements but have not increased significantly. The performance of government bureaucracy in a simple way can be measured by assessing the good quality of public services. Public service performance measurement is a very important aspect to see the achievement of service delivery to the community. Research on the implementation of birth certificate services is important to do, because the public as customer service has not felt satisfied both in terms of time, procedures and quality of service that has been provided. This research was conducted to determine the implementation and constraints encountered in efforts to improve birth certificate services at the Surabaya City Population and Civil Registration Service. The focus of observation includes service procedures, completion time, cost of services, facilities and infrastructure, competence of service providers and constraints faced. The method used in this study is a qualitative method using descriptive analysis. Interactive model data analysis which begins with the process of collecting data, simplifying data, presenting data, and giving recommendations with conclusions shows that the implementation of birth certificate services in the Surabaya City Population and Civil Registration Service is good or quality that can be seen from the reliability indicator responsiveness, assurance, attention and tangibles. The advice given, should the Surabaya City Population and Civil Registration Service increase public knowledge and should service the issuance of birth certificates at the Surabaya City Population and Civil Registration Service can be carried out optimally.